A Comprehensive Literature Review of Histopathology of Hepatocelullar Carcinoma - Wahyu Agus Prastyo; Artha Investari Nugraheni (International Medical Journal Corp. Ltd, 2024)
Background: The literature surrounding hepatocellular carcinoma (HCC) reveals a complex interplay of histopathological features, molecular genetics, and clinical implications that shape the understanding and management of this prevalent malignancy. Literature Review: The molecular and genetic markers associated with HCC are explored by (El-Nakeep, 2022), who address the high mortality rates associated with HCC and the complex relationship between cirrhosis and HCC development. This discussion emphasizes the necessity for further investigation into the molecular pathways underlying HCC progression. The role of imaging in diagnosis and management is reinforced by (Chartampilas et al., 2022), highlighting the importance of dynamic imaging techniques in accurately staging HCC and assessing treatment responses. Moreover, localized studies, such as that by (Sweed et al., 2022), contribute to the understanding of HCC's heterogeneous nature, emphasizing morpho-molecular classifications that guide diagnosis and treatment. The immune landscape, as discussed by (Gryziak et al., 2022), introduces the implications of immune cell interactions within the tumor microenvironment, suggesting that immune profiles should be considered alongside histopathological features in tailoring treatment strategies. The mutational landscape of HCC and the potential for precision medicine are examined by (Gorji et al., 2023), advocating for personalized therapeutic strategies that account for the genetic diversity of HCC. Finally, (Hyuk Choi & N. Thung, 2023) synthesize recent advancements in histological and molecular classification, emphasizing the importance of accurate pathological classification for effective management and prognostication. Conclusion: In conclusion, the literature collectively underscores the critical integration of histopathological analysis with molecular insights and clinical practices to enhance the understanding of HCC. This multifaceted approach is essential for improving diagnosis, treatment, and patient outcomes in the context of this complex malignancy.